Helminthiasis - Olayinka Okwa, Omolade (IntechOpen, 2020)
Helminthiasis is a disease caused by parasitic helminths such as flukes, tapeworms, filarial worms, and nematodes. These parasites cause diseases that pose serious health problems, especially in developing countries of the world. Helminthiasis is a reflection of poor socio-economic conditions, which impacts on the social life of victims and economic development. Parasitic helminths live in a variety of habitats in their hosts and are far more widespread than we think. Gastrointestinal helminths are the largest group that affects their host directly through feacal-oral routes. This book not only provides insight into antihelminthic resistance in livestock but it also discusses soil transmitted helminths in pregnant women and children and filariasis as a debilitating disease. The book covers the prevention and control of helminthiasis of which adequate diagnosis is crucial. This book helps to close the information gap on helminthiasis, which has otherwise been classified as belonging to the group of neglected diseases and overlooked as a serious cause of morbidity and mortality of humans and domestic animals. The information in this book proposes that helminthiasis needs more global attention.